Women, film, and law: cinematic representations of female incarceration - Bouclin, Suzanne (Law and society series, 2021)
"Women, Film, and Law convincingly argues that popular fictional depictions of women's imprisonment can illuminate the multiple forms of marginalization, social exclusion, and oppression experienced by criminalized women. While entertainment and profit constitute the driving force behind popular representations of women in correctional facilities, the creative influence of film and television also generates legal meaning. The women-in-prison (WIP) genre can leave viewers feeling both empathetic toward the women portrayed in these films and troubled about the crimes for which they find themselves incarcerated. Focusing on five exemplary WIP films and a television series, from 1933 to the present, Women, Film, and Law asks how fictional representations explore, shape, and refine beliefs about women who are incarcerated. WIP films grapple with women's liberation and subjugation, sexuality and sexual identities, forbidden desires, and physical and emotional imprisonment. They are also rich material for critical legal readings of the construction of the "female criminal" and the offences for which stock characters are convicted. From melodrama to exploitation, and from theatre screenings to on-demand film, television programs, and music videos, these media bring into view the legal, economic, and political structures that criminalize women differently from men, and that target those women who are already at the margins of society."--